Production of the Sesquiterpene Bisabolene From One‐ and Two‐Carbon Compounds in Engineered Methanosarcina acetivorans - Andrea Mentrup; Luca V. Scheitz; Theo Wallenfang; Michael Rother (Microbial Biotechnology)
ABSTRACT The isoprenoid bisabolene, one of the simplest monocyclic sesquiterpenes, is a natural plant product that, in addition to its biological function, serves as a precursor for many industrial products. Due to the low concentration of bisabolene and the long harvest cycle, industrial production of this isoprenoid in plants is economically challenging. Chemical synthesis of bisabolene also suffers from significant disadvantages, such as low yields, toxic side products and high costs. Archaea appear suitable producers of isoprenoids, as their membrane lipids consist of isoprenoid ethers, which are synthesised via a variant of the mevalonate (MVA) pathway. Archaeal model species have versatile metabolic capacities, which makes them potential candidates for biotechnological applications. Here, we engineered Methanosarcina acetivorans for production of α‐bisabolene from one‐carbon substrates by introducing a bisabolene synthase from Abies grandis. Expression of a codon‐optimised bisabolene synthase gene in M. acetivorans resulted in 10.6 mg bisabolene/L of culture. Overexpressing genes of the MVA pathway only slightly increased bisabolene yields, which, however, were reached much earlier during incubations than in the corresponding parent strain. The data presented argue for the suitability of M. acetivorans for the biotechnical production of certain isoprenoids.